Potential of enhanced efficiency nitrogen fertilizers in reducing nitrogen and carbon losses in a sandy soil integrated crop-livestock system - Oliveira, Clayton Luis Baravelli de; Cassimiro, Juliana Bonfim; Silveira, Daniel da Silva; Belisario, Matheus Parra; Heinrichs, Reges [UNESP]; Cassim, Bruno Maia Abdo Rahmen; Batista, Marcelo Augusto; Moro, Edemar (Elsevier, 2024)
The demand for food is increasing, which poses significant challenges to humanity's sustainable and sufficient food production. Using fertilizers with new technologies with a low environmental impact is becoming increasingly necessary. In this context, the industry has been creating alternatives to optimize the use of nitrogen (N) fertilizers, with the improvement of urea being crucial for sustainable agricultural production. The objective of this study was to assess the use of fertilizers with integrated technology, specifically urea NBPT + Duromide and formaldehyde urea, aiming to reduce N losses through ammonia (NH3-N) volatilization and, consequently, mitigate carbon dioxide (CO2) emissions in the integrated crop-livestock system (ICLS), thereby addressing the impacts of global warming. Evaluations were conducted over three agricultural years (2020/2021, 2021/2022, and 2022/2023). The pasture used was Urochloa Brizhanta cv. marandu, and soybeans (Glycine max L) were cultivated. The experimental design was a randomized complete block with four replications in a 3 × 4 factorial arrangement. The treatments consisted of three N sources: conventional urea (UrConv) for immediate release, formaldehyde urea (UrFormaldehyde) for slow release, and urea with urease inhibitor and Duromide technology (UrDuromide), combined with four rates (0, 100, 200, and 400 kg ha−1 of N). NH3-N volatilization data were subjected to nonlinear regression using a logistic model. NH3-N volatilization losses varied according to the rate and fertilizer, reaching up to 33% in UrConv. UrDuromide exhibited reduced efficiency over the evaluated years compared to UrConv, reducing losses by 52% in the first year, 46% in the second, and only 5% in the third. UrFormaldehyde showed less variability, ranging between 57% and 45% reduction in NH3-N losses. The effects on TOC and CO2 emissions followed similar trends, with UrConv causing the highest CO2 emissions and more significant TOC accumulation. UrFormaldehyde reduced CO2 by up to 8% compared to UrConv, while UrDuromide reduced it by 6% compared to UrConv in greenhouse gas emissions and consequently lower soil organic carbon accumulation. In conclusion, using technology to enhance efficiency in nitrogen fertilizers showed promising results in reducing greenhouse gas emissions, offering hope for a sustainable future and making it a viable alternative to conventional urea sources.
Keywords: Greenhouse effect; Sustainable agriculture; Urea formaldehyde; Urease inhibitor